A comparative 18F-FDG and an anti-PD-L1 probe PET/CT imaging of implant-associated Staphylococcus aureus osteomyelitis - Ren, Shu-Qi; Ma, Yuan; Fu, Li-Lan; Hu, Kong-Zhen; Liang, Hao-Ran; Yu, Bin; Tang, Gang-Hua (Frontiers in Cellular and Infection Microbiology, 2023)
Background Early and accurate diagnosis of infection-induced osteomyelitis, which often involves increased PD-L1 expression, is crucial for better treatment outcomes. Radiolabeled anti-PD-L1 nuclear imaging allows for sensitive and non-invasive whole-body assessments of PD-L1 expression. This study aimed to compare the efficacy of 18F-FDG and an 18F-labeled PD-L1-binding peptide probe (18F-PD-L1P) in PET imaging of implant-associated Staphylococcus aureus osteomyelitis (IAOM). Methods In this study, we synthesized an anti-PD-L1 probe and compared its efficacy with 18F-FDG and 18F-PD-L1P in PET imaging of implant-associated Staphylococcus aureus osteomyelitis (IAOM). The %ID/g ratios (i.e., radioactivity ratios between the infected and non-infected sides) of both probes were evaluated for sensitivity and accuracy in post-infected 7-day tibias and post-infected 21 days, and the intensity of 18F-PD-L1P uptake was compared with pathological changes measured by PD-L1 immunohistochemistry (IHC). Results Compared with 18F-FDG, 18F-PDL1P demonstrated higher %ID/g ratios for both post-infected 7-day tibias (P=0.001) and post-infected 21 days (P=0.028). The intensity of 18F-PD-L1P uptake reflected the pathological changes of osteomyelitic bones. In comparison to 18F-FDG, 18F-PDL1P provides earlier and more sensitive detection of osteomyelitis caused by S. aureus. Conclusion Our findings suggest that the 18F-PDL1P probe is a promising tool for the early and accurate detection of osteomyelitis caused by S. aureus.